2009
DOI: 10.1007/s00011-009-8034-0
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating osteopontin reduces angiotensin II-induced inflammatory activation in vascular smooth muscle cells

Abstract: This result suggested that OPN plays an important role in Ang II-induced inflammatory activation in VSMCs. The finding further supports OPN as a potential target for atherosclerotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…It meant that an OPN-dependent pathway was necessary in nicotine-induced inflammation. It accorded with our previous report in Ang II-mediated inflammation [16], and the study in PDA also obtained approximate results [13]. Therefore, our data, collectively, indicated that NFκB/OPN amplification loop existed in this pro-inflammatory process.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It meant that an OPN-dependent pathway was necessary in nicotine-induced inflammation. It accorded with our previous report in Ang II-mediated inflammation [16], and the study in PDA also obtained approximate results [13]. Therefore, our data, collectively, indicated that NFκB/OPN amplification loop existed in this pro-inflammatory process.…”
Section: Discussionsupporting
confidence: 92%
“…Both these studies suggest nicotine playing a synergetic role in Ang II-induced vascular disease. We reported that OPN played a central role in Ang IImediated inflammation in VSMC [16], and we found that nicotine induced OPN mRNA expression and protein release obviously in this study. Therefore, the role of OPN in nicotine-induced inflammatory response was evaluated.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…TNF ␣ and IL-1 ␤ both stimulate SMC FN expression [67] , and attachment to FN stimulates transient activation of NF-B [68] . Osteopontin deposition is enhanced in the atherosclerotic plaque, and osteopontin siRNA reduces Ang II-dependent secretion of IL-6 through an NF-B-and AP-1-dependent mechanism [69] . Matrix-specific cellular responses are thought to occur through the integrin family of matrix receptors.…”
Section: Matrix Composition In the Smc Inflammatory Phenotypementioning
confidence: 99%